Hypertension across a Woman's lifespan. (February 2023) - D'Ignazio, Tara; Grand'Maison, Sophie; Bérubé, Lyne; Forcillo, Jessica; Pacheco, Christine
Highlights: Hypertension is a leading risk factor for cardiovascular disease in women. Sex-specific factors, such as polycystic ovary syndrome, hypertension in pregnancy and menopause, modulate the risk of hypertension across the lifespan. By age 75, the prevalence of hypertens ion in women is higher than in men. Abstract: Hypertension is a leading risk factor for cardiovascular disease in women. Both traditional and sex-specific risk modifiers occurring from menarche to pregnancy to menopause modulate the risk of hypertension and adverse cardiovascular events. This review provides a narrative summary of risk and treatment of hypertension in women across the lifespan, from adolescence to the post-menopausal period, where each period represents a potential window for risk assessment, diagnosis, and appropriate treatment. Management of hypertension throughout a woman's life must be included in a holistic cardiovascular prevention approach for women in order to prevent future cardiovascular complications.